The effect of adding beebread to honey on the chemical composition of the resulting honey (Journal of Hama University, 2022)
The aim of this research is to determine the geographical location and scrape of bee bread collected from two different regions in the coastal region (north of Latakia) and the interior region (Al-Ghab region, rural Hama) for the year 2021, in the period between April and May of the same year.In order to know the effect of the difference of source on the chemical composition of bee bread, the results showed a higher content of bee bread collected from the interior region (Anise) of protein phenols and diastase number as well as fructose sugar and glucose compared with bee bread collected from the coastal region (citrus).The aim of the research was to add bee bread at a ratio of 60 grams per 1 kg of honey to two types of honey, citrus honey and aniseed honey. And studying the effect of this addition on the chemical composition, where the results showed the contribution of adding bee bread to both types of honey to raising the antioxidant capacity of honey added to it. As well as in improving the properties of honey resulting from the addition of bee bread to it in terms of its content of protein, phenols and diastase number.
Keywords: bee bread, honey, antioxidant capacity, phenols